Surface engineering of Rh-modified Pd nanocrystals by colloidal underpotential deposition for electrocatalytic methanol oxidation. Issue 10 (3rd March 2021) - Bao, Haibo; Xia, Shiyu; Wu, Fengxia; Li, Fenghua; Zhang, Ling; Yuan, Yali; Xu, Guobao; Niu, Wenxin
Abstract : Underpotential deposition of Rh on Pd nanocrystals directs the synthesis of surface-engineered Rh-modified Pd nanocrystals with superior electrocatalytic performances. Abstract : The development of methods to control the surface structures of metallic nanocatalysts is of vital importance for their application as heterogeneous catalysts in chemical conversions of energy and environmental and chemical engineering. The underpotential deposition (UPD) phenomenon has received considerable interest as a tool for the controllable synthesis of metal nanocrystals and engineering their catalytic performances. Herein, the discovery of UPD of Rh on Pd nanocrystals is reported. More importantly, the UPD of Rh is explored as a strategy to direct the synthesis of Rh-modified Pd nanocrystals with controllable shapes and surface structures. The mechanism of the UPD of Rh on Pd is elucidated in terms of electronegativity difference considerations. Compared with pristine Pd octahedral nanocrystals and commercial carbon-supported Pd catalysts, the Rh-modified Pd octahedral nanocrystals exhibit remarkable electrocatalytic performances during the methanol oxidation reaction in alkaline media. Our discovery heralds a new paradigm for UPD-mediated growth of metal nanocrystals and may provide a mechanistic understanding for the guided design of other colloidal UPD systems in the synthesis and surface engineering of metal nanocrystals.